Pacific approaches to fundraising in the digital age: COVID-19, resilience and community relational economic practices - de la Torre Parra L; Movono A; Scheyvens R; Auckram S (John Wiley and Sons, Inc., 2023)
The aim of this paper is to discuss how community relational economic practices in virtual spaces are effective in building resilience because they are borne of and sustained by familiar traditional Fijian values of collective work and social interdependence. The researchers adopted a pandemic-induced methodology, conducting online-based talanoa (fluid conversations between two or more people) with a number of people leading, or involved in, these initiatives. We also engaged with online community groups behind a number of initiatives. Examples are provided of online crowdfunding, livestreaming of concerts to solicit donations, and bartering facilitated by social media sites. To conclude, we stress the enduring nature of communal bonds and traditional systems which Pacific people readily adapt and translate into different forums and forms in the face of challenges such as the restrictions and financial hardships caused by COVID-19. The findings highlight that solesolevaki – a tradition of working together for a common cause – can also occur in the digital era: this demonstrates the deep connection of Fijian peoples and their sense of obligation to one another and to their culture, regardless of where they are in the world.
Keywords: adaptivity; community relational economic practice; COVID-19; diverse economies; resilience; virtual space